Comprehensive Physiology 2010
DOI: 10.1002/cphy.c090005
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Energy Metabolism, Proliferation, and Apoptosis in Pulmonary Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a fatal disease characterized by impaired regulation of pulmonary hemodynamics and excessive growth and dysfunction of the endothelial cells that line the arteries in PAH lungs. Establishment of methods for culture of pulmonary artery endothelial cells from PAH lungs has provided the groundwork for mechanistic translational studies that confirm and extend findings from model systems and spontaneous pulmonary hypertension in animals. Endothelial cell hyperproliferation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
103
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 159 publications
(269 reference statements)
14
103
1
1
Order By: Relevance
“…This model is supported by evidence showing that siRNA knockdown of S1P 2 expression or S1P 2 antagonism with JTE-013 (which is also a competitive antagonist of S1P 4 [19]) ablated the S1P-stimulated proliferation of human PASMC [17]. This report suggested that S1P/S1P 2 uses ERK-1/2 and STAT3 signaling to promote human PASMC proliferation [17], and which is significant as STAT3 activation has been shown to be involved in pro-survival and proliferative pulmonary vascular phenotypes associated with human PAH [3,20,21]. Finally, the S1P 2/4 antagonist, JTE-013 (8 mg/kg body weight, i/p) prevented and reversed pulmonary hypertension in the hypoxic mouse model [17], thereby confirming that S1P 2 is involved in S1P-stimulated vascular remodeling in this model.…”
Section: Sphingosine Kinase 1 and Hypertensionmentioning
confidence: 79%
“…This model is supported by evidence showing that siRNA knockdown of S1P 2 expression or S1P 2 antagonism with JTE-013 (which is also a competitive antagonist of S1P 4 [19]) ablated the S1P-stimulated proliferation of human PASMC [17]. This report suggested that S1P/S1P 2 uses ERK-1/2 and STAT3 signaling to promote human PASMC proliferation [17], and which is significant as STAT3 activation has been shown to be involved in pro-survival and proliferative pulmonary vascular phenotypes associated with human PAH [3,20,21]. Finally, the S1P 2/4 antagonist, JTE-013 (8 mg/kg body weight, i/p) prevented and reversed pulmonary hypertension in the hypoxic mouse model [17], thereby confirming that S1P 2 is involved in S1P-stimulated vascular remodeling in this model.…”
Section: Sphingosine Kinase 1 and Hypertensionmentioning
confidence: 79%
“…A disorder of proliferation and migration has been observed in human plexiform lesions (22), and more recent studies of hyperproliferative PAECs in PH have described an accompanying migratory phenotype (38). Such disordered migration may contribute to abnormal angiogenesis in PH -which in some cases has been linked to a proangiogenic and pathogenic remodeling of the pulmonary arteriole (39) and in other cases has been linked to a deficiency of angiogenesis (39) and a pruning of the entire pulmonary vascular tree. Consequently, our work places vessel stiffness, the YAP/TAZ-GLS1 axis, and gluta- , decreased glutamine/glutamate ratio (C), and increased aspartate (D) in an independent HIV-PAH patient cohort (n = 9) as compared with HIV-infected patients alone (n = 7).…”
Section: Discussionmentioning
confidence: 99%
“…X. Xu and S. Erzurum introduced the concept of increased glycolysis in the EC of PAH patients, potentially due to decreased mitochondrial function and increased ROS production (56). The historical work of Warburg (57), showing a predominance of glycolysis over respiration in tumors, was expanded by R. Tuder into the pathogenesis of PH (3).…”
Section: Discussionmentioning
confidence: 99%